KURANG EFEKTIFNYA SISWA DALAM PEMBELAJARAN SOSIOLOGI DI KELAS X SMA PGRI 1 PADANG - MAIYANTI, DESRINA - (Pendidikan Sosiologi, 2014)
This research is motivated by the lack of effective student learning in high school sociology classX. This study aimed to describe the cause of the lack of effectiveness of students in sociology aswell as describing the efforts of teachers in dealing with students who are less effective in teachingsociology.The theory used in this research by Skinner Behaviorism. The approach used in this study is aqualitative research method with descriptive type to give a detailed description of the reality understudy. Informants in this study amounted to as much as 7 students were less effective in teachingsociology. Data was collected through observation and in-depth interviews and documentation.The unit is an individual data analysis, and data analysis were used to stage data collection, datareduction, data presentation (data analysis), and the verification and conclusion.Based on the results of research conducted in PGRI SMA 1 Padang cause of the lack of effectivestudent learning in sociology, namely 1) the class conditions less conducive to learning, 2) parentsare less controlling and motivating students to learn, 3) teaching a less attractive environment, 4)facilities that use inadequate and unattractive, 5) the teacher was not to establish interaction andcommunication with students. Efforts of teachers to address students who are less effective inteaching sociology, namely 1) the approach and motivate Siwa, 2) Learn to use various media andmethods.